Exploitation and Resilience: The Singosari Community Faces Environmental Threats - Rico Tomboti; Khoiron Khoiron; Langgeng Rachmatullah Putra (Department of Public Administration, 2026)
This study examines the dynamics of Singosari residents' resistance to the Singhasari Special Economic Zone (SEZ) project, focusing on the discursive mechanisms that construct meanings of exploitation, local identity, and ecological injustice. The researcher used Van Dijk's theory-based Critical Discourse Analysis (CDA) that integrates text triangulation, social cognition, and context. The primary data consisted of protest banners from residents and narratives from community leaders, including Ki Ardhi Purbo Antono and Fatkul Ulum (Gus Ulum), while supporting data were obtained from international literature on environmental injustice and the failure of the Environmental Impact Assessment (EIA). The results show that the narrative